Diet and family support for the nutritional status of the elderly - Syaharuddin Syaharuddin; Tri Damayanti Samsul; Firmansyah Firmansyah (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Elderly is a natural process that all people who are blessed with a long life will definitely go through. Someone is said to be elderly if they are more than 60 years old and begin after retirement because their age experiences biological, physical, psychological, and social changes. Preliminary data regarding the number of older adults at the Pertiwi Community Health Center, Mariso District, Makassar City, in March 2023, 37 older adults were attending the elderly posyandu. This research aims to determine the relationship between diet and family support on the nutritional status of older people. The method in this research is a descriptive-analytical design with a cross-sectional study approach and sampling using a non-probability sampling technique with an accidental sampling approach and the Fisher exact test statistical test. The sample size in this study was 28 respondents. The results of this study showed a significant relationship between diet and the nutritional status of older people with a p-value = 0.001, and there was no meaningful relationship between the relationship between family support and the healthy group of older people with a p-value = 0.064. The conclusion is that the relationship between diet is more dominant on nutritional status than family support. Hence, the diet of older people needs to be considered to improve the nutritional quality of older people